2016
DOI: 10.3390/inorganics4020008
|View full text |Cite
|
Sign up to set email alerts
|

Hexacoordinate Silicon Compounds with a Dianionic Tetradentate (N,N′,N′,N)-Chelating Ligand

Abstract: Charge distribution within the whole molecules was analyzed by calculating the Natural Charges (NCs). Although these five compounds carry electronically different monodentate substituents, their constituents reveal rather narrow ranges of their charges (Si atoms: +2.10-+2.22; monodentate substituents:´0.54-´0.56; L 2´:´1 .02-´1.11).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 116 publications
0
2
0
Order By: Relevance
“…29 Gerlach, who conducted 76 qualitative interviews with women immigration detainees and former detainees in the UK, concluded that part of the harm stemmed from the indignity associated with 'the disconnect between their own perceived sense of being a "good" person, and their treatment at the hands of the Home Office'. 30 This was also concluded by Rivas and Bull, who examined the experiences of women held in long-term immigration detention in Australia. 31 They also found that women detainees 'experience this detention differently than their male counterparts'.…”
Section: The Harms Of Arbitrary Detentionmentioning
confidence: 74%
“…29 Gerlach, who conducted 76 qualitative interviews with women immigration detainees and former detainees in the UK, concluded that part of the harm stemmed from the indignity associated with 'the disconnect between their own perceived sense of being a "good" person, and their treatment at the hands of the Home Office'. 30 This was also concluded by Rivas and Bull, who examined the experiences of women held in long-term immigration detention in Australia. 31 They also found that women detainees 'experience this detention differently than their male counterparts'.…”
Section: The Harms Of Arbitrary Detentionmentioning
confidence: 74%
“…The Si-C bond (1.853(4) Å) is only marginally longer than in the starting silane MeSi(pyO) 3 (1.837(2) Å), thus hinting at only a weak Pd→Si lone pair donor action. At hexacoordinate silicon with trans-disposed stronger donor (e.g., another hydrocarbyl group [42,43], 2-pyridinethiolato N atom [28] or 8-oxyquinolinyl N atom [44,45]), one would expect a Si-C bond lengthening beyond 1.90 Å. The Pd-Cl bond (2.891(1) Å), however, is unexpectedly long, thus hinting at ionic dissociation.…”
Section: Reactions Of Mesi(pyo)3 With [Pdcl2(ncme)2] and Cuclmentioning
confidence: 99%